(untitled) (Journal of Bangladesh Academy of Sciences, 2021)
Based on the power generation model of photovoltaic modules, the effects of flight speed, altitude, time and area in solar aircraft on the performance of photovoltaic modules have been studied. As the flight speed increases, the power generated by the module increases but tends to saturate. When the conversion efficiency of photovoltaic modules is improved, the required power of the solar aircraft and the power generated by the photovoltaic modules are balanced at a faster flight speed. The power generated by the modules increases with the flight altitude but tends to saturate due to the drop of air temperature and the surface temperature of the module. The higher the altitude, the smaller is the atmospheric density, and atmospheric permeability, and the greater is the solar radiation intensity, and thus the power generated by the module increases. The power generated by the components is the strongest at noon. Battery performance is the strongest in summer and the weakest in winter, as the module’s performance is mainly determined by the intensity of solar radiation. Finally, the energy distribution of solar aircraft and long-time space flight has been discussed. J. Bangladesh Acad. Sci. 45(1); 73-83: June 2021